Tropical crops advisory selection system - Sahibin, Siti Safura Yasmin; Zeki, Akram M. (2011)
This paper involves analysing and designing a prototyping system that automates the evaluation of land. The main objective of this study is to eliminate the needs to rate the suitability of land areas for several land use types (LUTs) manually. Tropical Crops Selection Advisory (TROPSEL) will be able to auto select LUTs according to known land characteristics. This system also ensures that the LUTs searching process of entered land characteristics would be easier and faster.